Ocena przydatności parametrów przezklatkowego badania echokardiograficznego w diagnostyce choroby niedokrwiennej serca = The assessment of fitness parameters of transthoracic echocardiography in the diagnosis of coronary heart disease - Rafał Lenard; Urszula Zielińska; Magdalena Michalczak; Anna Sobieszczańska; Agata Barbara Smoleń (Kazimierz Wielki University, 2015)
Lenard Rafał, Zielińska Urszula, Michalczak Magdalena, Sobieszczańska Anna, Smoleń Agata. Ocena przydatności parametrów przezklatkowego badania echokardiograficznego w diagnostyce choroby niedokrwiennej serca = The assessment of fitness parameters of transthoracic echocardiography in the diagnosis of coronary heart disease. Journal of Education, Health and Sport. 2015;5(12):701-716. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45069 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A701-716 https://pbn.nauka.gov.pl/works/701302 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive           The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.12.2015. Revised 25.12.2015. Accepted: 29.12.2015.     Ocena przydatności parametrów przezklatkowego badania echokardiograficznego w diagnostyce choroby niedokrwiennej serca   The assessment of fitness parameters of transthoracic echocardiography in the diagnosis of coronary heart disease   Rafał Lenard1, Urszula Zielińska2, Magdalena Michalczak1, Anna Sobieszczańska3, Agata Smoleń1   1Katedra i Zakład Epidemiologii i Metodologii Badań Klinicznych, Uniwersytet Medyczny w Lublinie 2Klinika Neurochirurgii i Neurochirurgii Dziecięcej, Uniwersytet Medyczny w Lublinie 3Katedra i Zakład Ortopedii Szczękowej, Uniwersytet Medyczny w Lublinie     Streszczenie Wprowadzenie Choroby układu krążenia stanowią główną przyczynę zgonów w Europie. Przezklatkowe badanie echokardiograficzne TTE wykonuje się celem oceny anatomii serca, oceny kurczliwości globalnej i odcinkowej lewej komory, oceny aorty piersiowej oraz naczyń płucnych. TTE należy do podstawowych badań w diagnostyce choroby niedokrwiennej serca. Cel pracy Celem pracy była ocena przydatności parametrów przezklatkowego badania echokardiograficznego w diagnostyce zmian w naczyniach wieńcowych. Materiał i metody Badaniem objęto 197 osób, w wieku od 43 do 88 lat, którzy byli hospitalizowani z powodu choroby niedokrwiennej serca (106 osób - 53,9% ze stabilną chorobą niedokrwienną serca, 91 osób - 46,1% z ostrym zespołem wieńcowym - OZW). Wyniki badań U pacjentów z OZW z obniżeniem frakcji wyrzutowej lewej komory częściej występowały istotne zmiany w tętnicach wieńcowych  (p<0,0001). Wśród  chorych z ostrym zespołem wieńcowym częściej występowała obniżona frakcja wyrzutowa lewej komory (62,6%) w porównaniu z pacjentami ze stabilną chorobą niedokrwienną serca (24,5%) (p<0,0001). W subpopulacji osób z OZW częściej występowały odcinkowe zaburzenia kurczliwości (67,0%) w porównaniu do grupy  osób ze stabilną chorobą niedokrwienną serca (8,0%) (p<0,0001). Wnioski 1. Badanie echokardiograficzne powinno być wykonywane u każdego pacjenta z podejrzeniem choroby niedokrwiennej serca, jeżeli tylko nie opóźnia pilnej rewaskularyzacji mięśnia serca. 2. Badanie echokardiograficzne jest najważniejszym badaniem w diagnostyce różnicowej bólu w klatce piersiowej oraz pozwala na stratyfikację ryzyka zdarzeń sercowo-naczyniowych. 3. Do najważniejszych parametrów w diagnostyce ChNS należy ocena frakcji wyrzutowej oraz regionalnych zaburzeń kurczliwości mięśnia lewej komory. 4. Zmniejszenie frakcji wyrzutowej oraz regionalne zaburzenia kurczliwości lewej komory są charakterystyczne dla zawału mięśnia serca (STEMI, NSTEMI).   Słowa kluczowe: echokardiografia, choroba niedokrwienna serca, diagnostyka.   Abstract Introduction Cardiovascular diseases are the major cause of death in Europe. Transthoracic echocardiography (TTE) is one of the most important examination in the diagnosis of coronary artery disease (CAD). Aim of the study The aim of the study was to evaluate parameters of TTE in the diagnosis of coronary artery disease. Methods and results The study included 197 patients hospitalized with coronary artery disease (106 -53.9% with stable CAD, 91 - 46.1% with acute coronary syndrome - ACS). The major atherosclerotic changes in the coronary arteries were more frequent in males, in patients with ACS and reduction of left ventricular ejection fraction (p<0.0001). In patients with ACS left ventricular ejection fraction was more frequent decreased (62.6%) compared to patients with stable coronary artery disease (24.5%) (p <0,0001). In patients with ACS segmental wall motion abnormalities were more frequent 61/91 (67.0%) compared to patients with stable CAD 9/106 (8.0%) (p<0.0001) Conclusions: 1. The echocardiography should be performed in every patient with suspected coronary heart disease, if only it doesn't delay urgent revascularization of the heart muscle. 2. The echocardiography is the most important examination in the differential diagnosis for the chest pain and allows the assessment of risk stratification for cardiovascular events. 3. The most important parameter in the diagnosis of coronary heart disease is the assessment of the ejection fraction and regional wall motion abnormalities of the left ventricle. 4. The reduction in ejection fraction and regional left ventricular wall motion abnormalities are characteristic for myocardial infarction (STEMI, NSTEMI).   Keywords: echocardiography, coronary artery disease, diagnosis.